Full-scale treatment of landfill leachate by using the mechanical vapor recompression combined with coagulation pretreatment. (August 2017) - Ye, Zhi-Long; Hong, Yingping; Pan, Songqing; Huang, Zhiqiang; Chen, Shaohua; Wang, Wei
Highlights: Full-scale mechanical vapor recompression was applied on leachate treatment. (Mg0.06 Ca0.94 )(CO3 ) and humics was the main components of MVR scale. Scale cleaning method of adding sulphamic acid and then NaOH was developed. Coagulation pretreatment reduced the treatment cost significantly. Abstract: Landfill leachate contains high concentrations of organic compounds and ammonium, and the presence of heavy metal ions, which normally requires expensive and complex treatment processes. In this study, full-scale experiments were implemented to evaluate the feasibility of mechanical vapor recompression (MVR) treating leachate. Results revealed that despite the drastic changes of influent pollutant concentrations, MVR system possessed the ability to reduce most of the pollutants and guarantee the effluent in compliance with the discharge limits of Chinese Standard. Fouling analyses revealed that the main components in the fouling were crystalline (Mg0.06 Ca0.94 )(CO3 ), combining with humus and silicon compounds. A fouling cleaning method was developed with the adding sequence of first sulphamic acid and then NaOH, which could remove 88.62% fouling. Although fouling was inevitable for MVR treating leachate, coagulation pretreatment removed large amounts of COD, BOD5, total nitrogen, ammonium and total phosphorus, with the respective means of 68.4%, 69.4%, 81.0%, 84.1% and 81.4%, and thereafter reduced the treatment cost 27.4% from 47.06 RMB (6.92 US dollars)/m 3 to 34.15 RMB (5.02 US dollars)/m 3 . These outcomes provided that in addition to the combination method of biological removal process with membrane technology, MVR process was another feasible solution for leachate treatment.